Принципы построения искусственных голосообразующих аппаратов - Кратюк, О. В.; Дацок, О. М. (ХНУРЕ, 2019)
This work is devoted to modern developments in the field of medical technology, namely, voice-forming devices used in the event of throat cancer, as a result of the removal of the larynx, the formation of a tracheostomy and for people with other speech disorders. The principle of physiological and technical work of voice-forming devices is described.
Keywords: аппарат голосообразующий искусственній; колебания мембрані